Embolic Diseases Unusual Therapies and Challenges - Firstenberg, Michael S. (IntechOpen, 2017)
Embolic complications of common, or sometimes uncommon, medical issues represent a significant management challenge. In addition, special populations might require unique approaches to prevention and primary disease management. Similarly, unusual embolic problems can manifest as both diagnostic and therapeutic challenges. Despite evolving guidelines to the prevention, diagnosis, and management of common diseases that can result in embolic complications, unfortunately, for many problems, such guidelines, randomized trials, or even recommendations based upon high-quality literature are lacking. Several chapters in this book are dedicated to summarizing the available data and experiences to help guide bedside care. The goal of this book is to emphasize some of the more unusual presentations and diagnostic and management aspects of embolic complications. The pathophysiologies and prevention strategies in unique patient populations are also emphasized. Clearly, a multidisciplinary team approach is critical to dealing with all aspects of these unusual and perplexing problems.